A criança e o consumo na escola - Sousa Junior, Wilson Rodrigues de (2009)
This research aims to understand how the choice and children's use of consumer goods related to their school, the meanings of these goods for children and the strategies they use to get what they want. To attain the goal we developed a literature on the t